Educational intervention on description of the insulin delivery technique: randomized clinical trial - Moura, Tatiana Victória Carneiro (2020)
Objective: to analyze the effect of educational intervention on insulin delivery technique. Methods: randomized clinical trial, carried out with 79 patients with Diabetes Mellitus, in two groups, 42 from the control group and 37 from the intervention. Four telephone calls were made in two months to the intervention group. The control group received only conventional follow-up. Results: when comparing the application of insulin in the pre and post-test, there was no significant difference (p>0.05) in the control group, but an improvement of 80.0% in the correct answers on the appropriate technique, with p<0.021 . In the intergroup comparison, the description of self-administration of insulin, after the telephone intervention, was better in 70.0% of the items, with p<0.030. Conclusion: the educational intervention via telephone improved the description of the technique of insulin application in patients with Diabetes Mellitus and their caregivers. Brazilian Registry of Clinical Trials number U1111-1228-3200.